Forecasting bitcoin's volatility: Exploring the potential of deep-learning - Pratas, Tiago Emanuel Teixeira (2022)
The importance of using the right statistical, mathematical and computational tools can highly influence the decision-making process. With the recent computational progress, Deep Learning methodologies based on Artificial Intelligence seem to be pointed out as a promising tool to study financial time series, characterised by out-of-the-ordinary patterns. Cryptocurrencies are a new asset class with several specially interesting characteristics that still lack deep study and differ from the traditional time series. Bitcoin in particular is characterised by extraordinary high volatility, high number of structural breaks and other identified characteristics that might further difficult the study and forecasting of the time series using classical models. The goal of this study is to critically compare the forecasting properties of classic methodologies (ARCH and GARCH) with Deep Learning Techniques (with MLP, RNN and LSTM architectures) when forecasting Bitcoin’s Volatility. The empirical study focuses on the forecasting of Bitcoin’s Volatility using such models and comparing its forecasting quality using MAE and MAPE for one, three- and seven-day’s forecasting horizons. The Deep learning methodologies show advantages in terms of forecasting quality (when we take in consideration the MAPE) but also require huge computational costs. Diebold-Mariano tests were also performed to compare the forecasts concluding the superiority of Deep Learning Methodologies.